2018
DOI: 10.2174/1573403x14666180524100608
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bipolar Radiofrequency Catheter Ablation in the Treatment of Cardiac Arrhythmias

Abstract: To allow wider clinical application the efficiency and safety of bipolar ablation need to be verified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Although steam-pop-related complications were rare in the clinical studies, 10,11 caution is required because experimental studies using a relatively high energy delivery showed a high incidence of steam-pop during BIP ablation. 16,17 The results of this study were similar to the previous clinical and experimental reports on UNIP ablation, 6,7 ) with transmural lesion and without steam-pop, and closed triangle is RF applications (8 times) both with transmural lesion and steam-pop. Averaged myocardial thickness in each 5-ohm-step of TID (Panel A) and in each 5%-step of %TID (Panel B) is shown in the lower column.…”
Section: Steam-pop and Its Predictorssupporting
confidence: 88%
See 1 more Smart Citation
“…Although steam-pop-related complications were rare in the clinical studies, 10,11 caution is required because experimental studies using a relatively high energy delivery showed a high incidence of steam-pop during BIP ablation. 16,17 The results of this study were similar to the previous clinical and experimental reports on UNIP ablation, 6,7 ) with transmural lesion and without steam-pop, and closed triangle is RF applications (8 times) both with transmural lesion and steam-pop. Averaged myocardial thickness in each 5-ohm-step of TID (Panel A) and in each 5%-step of %TID (Panel B) is shown in the lower column.…”
Section: Steam-pop and Its Predictorssupporting
confidence: 88%
“…However, in several studies, 9,15 these indexes were reported to be insufficient to prevent the occurrence of steam‐pop. Although steam‐pop‐related complications were rare in the clinical studies, 10,11 caution is required because experimental studies using a relatively high energy delivery showed a high incidence of steam‐pop during BIP ablation 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial discrepancy within the available ex vivo studies regarding steam pop incidence during BPA 10,30 . Importantly, clinical studies have not reported any major complications while ablating in the bipolar mode for miscellaneous arrhythmias 15 . This agrees with our evidence, albeit nonsignificant, of a lower incidence of steam pop in BPA.…”
Section: Discussionsupporting
confidence: 80%
“…A number of in vitro, in vivo, and small‐cohort clinical studies 11‐16 have compared UPA and BPA, suggesting the superiority of the bipolar configuration in creating deep and transmural lesions compared to the standard unipolar configuration 15 . Most of the studies on this topic have used solely linear macroscopic width and depth to characterize the geometry of the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…By this configuration, the applied energy produces a rapid rise in tissue temperature and consequent thermal injury (23). Due to this distinctive mechanism of lesion formation, bipolar ablation represents an appealing alternative for creating permanent transmural lesions, especially in deep arrhythmia substrates, as left ventricle papillary muscles, interventricular septum, left ventricular mid-myocardium, or fat-insulated epicardium (24,25).…”
Section: Bipolar Radiofrequency Ablationmentioning
confidence: 99%